PERANCANGAN TATA KELOLA PENYIMPANAN REKAM MEDIS DI KLINIK PRIMA HUSADA - Sri Wahyuningsih; Yuda Syahidin; Erix Gunawan (INFOKES (Informasi Kesehatan), 2023)
This study aims to determine the Management of Medical Record Storage at Prima Husada Clinic. The research methodology used in this study is a qualitative descriptive method, in which the researcher provides an overview and explanation of the research results obtained in a complete, comprehensive manner related to the Management of Medical Record File Storage at the Prima Husada Clinic by looking directly at the realities in the field. It can be concluded that the medical record unit at the Prima Husada Clinic does not yet have standard operating procedures related to the management of storage and storage of medical records, which are still not in accordance with the applicable regulations, both in the medical record numbering system and in the Prima Husada Clinic, they still use a manual numbering system. The solution to this problem is to carry out medical record storage in accordance with applicable standard operating procedures and it is necessary to plan budgeting costs for purchases or additions needed at the Prima Husada Clinic medical record unit so that management of medical record storage can be carried out in accordance with applicable standard operating procedures. Keywords: Design, Governance, Medical Record Storage.